LANDASAN FILOSOFIS KEBIJAKAN PENGEMBANGAN KURIKULUM BAHASA ARAB - Tricahyo, Agus (STAIN Ponorogo, 2013)
Abstract: Curriculum is a component that takes an important role in the education system. Curriculum is formulated as the objectives that must be achieved so that the educational programs are able to run clearly and effectively. In addition, thecurriculum provides an understanding of learning that ought to be owned by each student. The development of Arabic curriculum is an ongoing process that should always be conducted continuously. If it is not, the curriculum has become obsoleteor outdated. Nevertheless, the curriculum development cannot be done with minimal effort or carelessly. The Arabic curriculum cannot be developed carelessly or improperly. In order toproduce a qualified Arabic curriculum, it requires some substantial foundations, for instance the religious foundation, in which the purposes of Arabic education cannot be separated from the goal of understanding the study of Islam with its various science, philosophical, juridical, or linguistics; the differences laid on the way or technique in teaching the language influenced by different views on seeing the nature of language, analyzing and describing the language, psycholinguistics, sociolinguistics, and the foundation of science and technology. Hence, the curriculum should be able to accommodate and anticipate the pace of developments in science and technology.